Random Fiber Array Generation Considering Actual Noncircular Fibers with a Particle-Shape Library - Myeong-Seok Go; Shin-Mu Park; Do-Won Kim; Do-Soon Hwang; Jae Hyuk Lim (Applied Sciences, 2020)
In this work, we generated a set of random representative volume elements (RVEs) of unidirectional composites considering actual noncircular cross-sections and positions of fibers with the aid of a shape-library approach. The cross-section of the noncircular carbon fiber was extracted from the M55J/M18 composite using image processing and a signed-distance-based mesh trimming scheme, and they were stored in a particle-shape library. The obtained noncircular fibers randomly chosen from the particle-shape library were applied to random fiber array generation algorithms to generate RVEs of various fiber volume fractions. To check the randomness of the proposed RVEs, we calculated spatial and physical metrics, and concluded that the proposed method is sufficiently random. Furthermore, to compare the effective elastic properties and the maximum von Mises stress in the matrix, it was applied to composite materials with different relative ratios of elastic moduli of M55J/M18 and T300/PR319. In the case of T300/PR319 having a high <semantics><mstyle mathvariant="bold" mathsize="normal">R</mstyle><mstyle mathvariant="bold" mathsize="normal">R</mstyle>T</semantics> (relative ratio of the transverse elastic moduli), simulation results were deviated up to about 5% in the effective elastic properties and 13% in the maximum von Mises stress in the matrix according to the fiber shapes.